A Comparison of class I malocclusion treatment outcomes with and without extractions using an ABO grading system for dental casts and radiographs - Bunga Ayub Rukiah; Amalia Oeripto; Nurhayati Harahap (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Class I malocclusion can be treated with or without resort to extraction. However, despite the indications, a controversy is still ongoing as to whether one option is preferable to another. One of the most frequent controversies centers on whether treatment involving extractions will produce superior results than treatment not culminating in extraction. Purpose: This study aimed to compare the results of treating class I malocclusion with extractions and those without extraction using an ABO grading system. Methods: Comparing ABO scores in patients’ dental casts and radiographs with class I malocclusion with and without extraction. Observational research incorporating case control methods was conducted involving 40 patients with class I malocclusion. Samples were divided into two groups, one treated with extraction (group E) and the other without extraction as the control group (K). The results of the treatment were measured and assessed using eight variables of the ABO Grading System. Results: The total score for the group treated with extractions was 23.65±7.82, while that for group K was 26.50±7.02. There was no significant difference in the total score between the two groups. Nevertheless, class I malocclusion treated with extraction had a lower score than without extraction. Conclusions: There was no difference in the total score of the ABO grading system for class I malocclusion patients treated with and without extractions.